2021
DOI: 10.1055/a-1638-5783
|View full text |Cite
|
Sign up to set email alerts
|

Regio- and Stereoselective Addition of Brønsted Acids to Yndiamides: Synthesis of N,O,N- and N,S,N-Trisubstituted Ketene Acetals

Abstract: Yndiamides, N,N-disubstituted alkynes, are versatile building blocks for the synthesis of nitrogen-containing organic molecules. Unlike ynamides, relatives that are inherently polarized by a single nitrogen substituent, their pseudo-symmetric nature renders regioselective reactions challenging. Here we report investigations into the regioselective addition of Brønsted acids to non-symmetric yndiamides, a reaction that delivers N,O,N- and N,S,N-trisubstituted ketene acetals with excellent regio- and stereoselec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In the oxidative functionalization of yndiamides via α‐ oxo gold carbenes, [8] we had found that steric effects afforded superior regiocontrol than electronic differentiation. [6b] Pleasingly, exploration of steric effects in the regioselective functionalization of non‐symmetric yndiamides with isoxazoles revealed a similar trend (Scheme 2 ). A series of yndiamides ( 1 b – 1 d ) bearing varying levels of steric difference between the two nitrogen atoms were subjected to functionalization with 5‐methylisoxazole (Scheme 2 a); as the steric bulk of one of the alkyl groups increased relative to the other n‐ Bu substituent, regioselectivity increased up to 9 : 1 for yndiamide 1 d ( n ‐Bu vs. c‐ Hex, 2 da / 2 da’ ).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…In the oxidative functionalization of yndiamides via α‐ oxo gold carbenes, [8] we had found that steric effects afforded superior regiocontrol than electronic differentiation. [6b] Pleasingly, exploration of steric effects in the regioselective functionalization of non‐symmetric yndiamides with isoxazoles revealed a similar trend (Scheme 2 ). A series of yndiamides ( 1 b – 1 d ) bearing varying levels of steric difference between the two nitrogen atoms were subjected to functionalization with 5‐methylisoxazole (Scheme 2 a); as the steric bulk of one of the alkyl groups increased relative to the other n‐ Bu substituent, regioselectivity increased up to 9 : 1 for yndiamide 1 d ( n ‐Bu vs. c‐ Hex, 2 da / 2 da’ ).…”
Section: Resultsmentioning
confidence: 88%
“…The pseudosymmetry of yndiamides presents a challenge and opportunity for regioselective functionalizations, which could enable differentiation of the pyrrole nitrogen substituents. In the oxidative functionalization of yndiamides via α‐ oxo gold carbenes, [8] we had found that steric effects afforded superior regiocontrol than electronic differentiation [6b] . Pleasingly, exploration of steric effects in the regioselective functionalization of non‐symmetric yndiamides with isoxazoles revealed a similar trend (Scheme 2).…”
Section: Resultsmentioning
confidence: 91%